2007
DOI: 10.1086/520683
|View full text |Cite
|
Sign up to set email alerts
|

A Seronegative Case of HIV-1 Subtype C Infection in Botswana

Abstract: We report the first case, to our knowledge, of antibody-negative human immunodeficiency virus type 1 (HIV-1) subtype C infection, which was identified during screening for acute HIV-1 infection in Botswana. Results of tests for HIV-1 antibodies were consistently negative, including rapid and regular enzyme-linked immunosorbent assay and Western blot. The nonrecombinant HIV-1 subtype C infection was confirmed by viral genotyping within the gag, pol, and env genes. The period between referral of the patient in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Although HIV-1 subtyping was not performed systematically for all individuals included in the seven BHP cohorts analyzed, our previous studies provide strong evidence for the overwhelming dominance of HIV-1 subtype C as the etiologic agent of the HIV/AIDS epidemic in Botswana [27], [39], [40], [41]. According to the HIV Sequence Database at LANL [42], 99.4% of the deposited 1,425 sequences from Botswana belong to HIV-1 subtype C. Therefore, we assume that the vast majority of subjects in this study are infected with HIV-1 subtype C.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although HIV-1 subtyping was not performed systematically for all individuals included in the seven BHP cohorts analyzed, our previous studies provide strong evidence for the overwhelming dominance of HIV-1 subtype C as the etiologic agent of the HIV/AIDS epidemic in Botswana [27], [39], [40], [41]. According to the HIV Sequence Database at LANL [42], 99.4% of the deposited 1,425 sequences from Botswana belong to HIV-1 subtype C. Therefore, we assume that the vast majority of subjects in this study are infected with HIV-1 subtype C.…”
Section: Methodsmentioning
confidence: 98%
“…The study was designed to evaluate potential trends between viral load and viral genetic diversity in acute and early HIV-1 subtype C infection, to determine the relationship between virologic parameters and viral set-point, and to identify immunological parameters that correlate with viral set-point in primary HIV-1 subtype C infection. All subjects included in the longitudinal analysis were genotyped and were found to be infected with HIV-1 subtype C. Results of the study were reported elsewhere [27], [39], [41], [43], [44], [45]. The primary infection cohort was comprised of individuals with estimated time of seroconversion.…”
Section: Methodsmentioning
confidence: 99%
“…The simultaneous detection of HIV antigens (p24) and anti-HIV antibodies by fourth-generation assays reduced the window period. Despite these efforts, the performance of certain serological assays is actually still suboptimal, although reliable HIV testing is a critical entry point for patients in need of ART [24][25][26][27].…”
Section: Genetic Diversity and Hiv Diagnosismentioning
confidence: 99%
“…Inclusion of HIV-1 group O antigens or the use of broadly cross-reactive antigens reduced limitations related to the high genetic diversity of HIV [5] and the simultaneous detection of HIV antigens (p24) and anti-HIV antibodies by fourth generation assays reduced the window period [6], [7]. Despite these efforts, the performance of certain serological assays is still suboptimal as illustrated by some studies [8][10] and the high rate of HIV indeterminate results generated by HIV serological tests remains a major concern in African countries [11][13].…”
Section: Introductionmentioning
confidence: 99%